An empirical analysis of the factors pushing the educated youth in crimes: evidence from Pakistan / Saeed ul Hasan Chishti - Hasan Chishti, Saeed ul (2014)
Education is the foundation of economic, social, political, spiritual and cultural development of a country and education youth is the future of every nation. But unfortunately there are some forces and factors which influence educated youth to commit crimes in the context of Pakistan. These forces may be social, socio-economic, political or cultural etc. This study identified these forces and causes of crimes in the educated youth which may be helpful for the parents, teachers, employers, planners, policymakers, police, courts and also for the criminals themselves to know what are the forces pushing them in the hell of crime and how they can get rid of such forces. In this study, data were collected from jails/prisons of different cities of Pakistan through questionnaire and interview. Data analysis comprised on chi-square testing method. Results indicated the weaknesses and flaws in planning, organizing, and controlling public sector, due to which a great number of people indulge in criminal activities.